Effects of imidazolium ionic liquids on skin barrier lipids - Perspectives for drug delivery - Paraskevopoulos, Georgios; Fandrei, Ferdinand; Kumar Pratihast, Ajit; Paraskevopoulou, Anna; Panoutsopoulou, Eleni; Opálka, Lukáš; Singh Mithu, Venus; Huster, Daniel; Vávrová, Kateřina (Journal of colloid and interface science, 2024)
Ionic liquids (ILs) have great potential to facilitate transdermal and topical drug delivery. Here, we investigated the mechanism of action of amphiphilic ILs 1-methyl-3-octylimidazolium bromide (C8MIM) and 3-dodecyl-1-methylimidazolium bromide (C12MIM) in skin barrier lipid models in comparison to their complex effects in human skin. C8MIM incorporated in a skin lipid model was a better permeation enhancer than C12MIM for water and model drugs, theophylline and diclofenac. Solid state 2H NMR and X-ray diffraction indicated that both ILs prefer the cholesterol-rich regions in skin lipids without significantly perturbing their lamellar arrangement and that C8MIM induces the formation of an isotropic lipid phase to a greater extent compared to C12MIM. C12MIM applied topically to the lipid model or human skin as a pretreatment was more potent than C8MIM. When co-applied with the drugs to human skin, aqueous C12MIM was more potent than C8MIM in enhancing theophylline permeation, but neither IL affected (even decreased) diclofenac permeation. Thus, the IL's ability to permeabilize skin lipid barrier is strongly modulated by its ability to reach the site of action and its interactions with drug and solvent. Such an interplay is far from trivial and requires detailed investigation to realize the full potential of ILs.
Keywords: Lipids; Diclofenac; Lipid model; Permeation; Skin barrier; diklofenak; lipidy; Solid-state NMR; Transdermal drug delivery; Humans; Ionic Liquids; Ionic liquid; Administration, Cutaneous; aplikace kožní; Theophylline; theofylin; lidé; iontové kapaliny